O metodę w filozofii - Koj, Leon (Filozofia Nauki, 1999)
The paper contains introductory remarks and is conceived of as a part of a larger project. First of all decisions are made as to the choice of an adequate concept of philosophy (which does not exclude other concepts of this field of interest). Among others philosophy as a very general domain of considerations is contrasted to logic and mathematics. Methods for philosophy are described in the way the natural sciences do it: methods are schemes for repeatable actions which in similar circumstances result in similar or identical outcomes irrespective of the philosopher's (the performer's) views. Philosophers very often neglect repeatability and similarity of effects. Kazimierz Twardowski's method of the elimination of contradiction (cf. his paper „On the so-called relative truths”) is put forward as a paragon of further important methods of philosophy.